“If You Want Anything, You Have to Fight for It”: Prisoner Strikes at Kingston Penitentiary, 1932–1935 - Willis, Cameron (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2022)
For four days in October 1932, during the height of the Great Depression, prisoners at Kingston Penitentiary revolted. They took control of their workshops and brought the convict labour regime to a halt, until the guards and militia violently regained control. This revolt was the culmination of more than a year of organizing and collective actions. Prisoners wrote manifestos, participated in work refusals, elected representatives, and developed a sophisticated critique of the conditions of their incarceration and the penitentiary administration. Using a unique collection of archival documents, this article closely examines the complaints, criticisms, fears, hopes, and frustrations of the incarcerated, whose demands and goals are crucial for understanding how and why the prisoner revolt unfolded as it did. I argue that the prisoners at Kingston Penitentiary, by striking and organizing to assert their dignity, democratically organized their lives and ensured a “fair deal” should be considered part of the Depression-era protests of the unemployed, imprisoned, and marginalized.